Paleozoic – Mesozoic and Eocene Outcrops in the North Sumatra Basin and their Implication to New Exploration Play Concept - Fatrial Bahesti (Berita Sedimentologi, 2017)
Paleozoic – Mesozoic and Eocene hydrocarbon plays in the North Sumatra Basin are still under-explored although they have been recognized for many years. The Paleozoic – Mesozoic play consists of Peusangan Group (Permian – Triassic) and Woyla Group (Jurassic – Cretaceous), which are overlain by Eocene – Early Oligocene Tampur carbonate/dolomite and onlapped by lacustrine Oligocene Bampo/Bruksah sediments. The Eocene play is represented by the Tampur Formation, which is a widespread carbonate/dolomite platform covering pre-rift sediments in the basin. A new mature source rock layer and highly permeable secondary porosity were observed in the Eocene Tampur carbonate outcrops. This finding suggests a possible new petroleum system involving the Eocene Tampur Formation as both source and reservoir.Identifying a new play concept and petroleum system in the Paleozoic – Mesozoic and Eocene sediments of the North Sumatra Basin will have important implications for future exploration, because it may lead to discovering potentially large hydrocarbon accumulation within naturally-fractured and/or karst reservoirs. Paleozoic – Mesozoic and Eocene petroleum systems in the basin at the moment are a subject of an ongoing study incorporating outcrops, core and seismic data.